Penguatan Usaha Tenun Ikat Tatin di Desa Blatatatin Kecamatan Kangae - Sarly, Margaretha Avitha; Nuran, Febrianti Rolivani Agatha; Maru, Maria Yasniana; Sareng, Eustacia Febylita (EDUPEDIA Publisher, 2023)
This community service aims to strengthen the management of calculating the cost of production, cost of goods sold and marketing strategies in terms of implementing accounting so that the financial reports produced are in accordance with accounting principles. It is hoped that this PKM activity can support the Tatin ikat weaving group in achieving good governance. To achieve good governance, Ikat Tatin Weaving must implement cost of production, cost of goods sold and marketing strategies. The method used in this PKM is Skills Training in the form of training on the application of cost of production, cost of goods sold and marketing strategies via social media. The participants in the activity were women from the ikat tatin weaving group. The results obtained from this activity are that the public understands the calculation of the cost of production, cost of goods sold and marketing strategies via digital platforms (Facebook). Keywords: Calculation of cost of goods manufactured, cost of goods sold and marketing strategy